Study on Emotional Intelligence and Stress Tolerance of Diabetic Physical Exercising and Diabetic Nonphysical Exercising Peoples on Critics - W. Vinu (Recent Developments in Medicine and Medical Research Vol. 10, 2021)
Aim: Objective of the study is to enlighten the need and importance of physical exercise in developing psychological wellbeing in diabetic peoples. Introduction : Physical exercise is the determine way to upsurge stress tolerance and assistances to uphold a sense of emotional wellbeing. Place and Duration of Study: Chidambaram, Cuddalore district, Tamilnadu, India. 1 year. Methodology: For this study a normative survive method was used to collect data from diabetic physical exercising and diabetic nonphysical exercising people from Chidambaram, Cuddalore district, Tamilnadu, India. This investigate is an attempt to analyse and interpret diabetic physical exercising and diabetic nonphysical exercising people on the psychological aspect of EI. The problem of this study is a comparison of on EI of diabetic physical exercising and diabetic nonphysical exercising peoples. The sample in the present study was limited to 60 nondiabetic and 60 diabetic people. Results: The result shows that the ‘r’ value obtained from the variable emotional stability and self- development on the sample of 60 on stress tolerance of diabetic physical exercising group was identified as 0.34 and 0.35 which was significant at 0.01 this shows that here remained a positive relationship between stress tolerance with emotional stability, Stress tolerance with self- development. When emotional stability increases stress tolerance increases when self- development develops stress tolerance increases. The diabetic non-physical exercising and diabetic physical exercising group significantly differ in their stress tolerance, comparatively, the mean value of 73.81 for diabetic physical exercising people with the mean value of 71.79 diabetic nonphysical exercising people is less. Hence it is proved that diabetic physical exercising people have more stress tolerance than diabetic nonphysical exercising people. This indicates that comparatively diabetic physical exercising people can withstand when deprived and tolerate critics of others because diabetic physical exercising people are more stress-tolerant when compared to diabetic nonphysical exercising people. The result of the diabetic physical exercising group’s ’r’ value obtained from the variable EI on the sample of 60 on stress tolerant was identified as 0.25 which was significant at 0.05. Conclusion: There was a positive relationship between stress tolerance with EI which specifies that when EI increases stress tolerance increases for diabetic physical exercising person’s vice versa.